Consumer Shopping Behaviour - An Empirical Study: (An Analysis with Reference to Select Areas of Andhra Pradesh) - Dr. B. Satyavani, (International Journal of Advanced Science and Technology, 2020)
Modern marketing is primarily concerned with creation of consumers. The present-day business men aim at ‘customer delight’ rather than just customer satisfaction. In fact, todays marketing is producing the products in the way the customers want, pricing them at an acceptable range, promoting them in the ways and means aspired by the customers, and delivering them at the place they want, ultimately aiming at not just satisfying but delighting them. Thus, what, when, how, for how much and where……everything is decided by the customers. To be profitable in business, marketers need to answer all these questions and find solutions in the form of different marketing strategies.